Transition between multimode oscillations in a loaded hair bundle - Wu, Fuqiang; Wang, Runxia (Chaos (Woodbury, N.Y.), 2019)
In this paper, we study the dynamics of an autonomous system for a hair bundle subject to mechanical load. We demonstrated the spontaneous oscillations that arise owing to interactions between the linear stiffness and the adapting stiffness. It is found that by varying the linear stiffness, the system can induce a weakly chaotic attractor in a certain region where the stable periodic orbit is infinitely close to a parabolic curve composed of unstable equilibrium points. By altering the adapting stiffness associated with the calcium concentration, the system is able to trigger the transition from the bistable resting state, through a pair of symmetric Hopf bifurcation, into the bistable limit cycle, even to the chaotic attractor. At a negative adapting stiffness, the system exhibits a double-scroll chaotic attractor. According to the method of qualitative theory of fast-slow decomposition, the trajectory of a double-scroll chaotic attractor in the whole system depends upon the symmetric fold/fold bifurcation in a fast system. Furthermore, the control of the adapting stiffness in the improved system with two slow variables can trigger a new transition from the bistable resting state into the chaotic attractor, even to the hyperchaotic attractor by observing the Lyapunov exponent. At the request of the authors, this article is being retracted effective 13 April 2020.